Deleuze and evolutionary theory - Bennett, Michael James; Posteraro, Tano S. (Deleuze connections., 2019)
"Deleuze and Evolutionary Theory gathers together contributions by many of the central theorists in Deleuze studies, who have led the way in breaking down the boundaries between philosophical and biological research. They focus on Deleuze and Guattari's engagements with evolutionary theory across the full range of their work, from the interpretation of Darwin in Difference and Repetition, to the symbiotic alliances of wasp and orchid in A Thousand Plateaus, and explore the anthropological, social and biopolitical significance of the convergences and divergences between philosophy and evolutionary science"--Back cover